An Evaluation of the Effects of Very Difficult Goals. Issue 1 (2nd January 2018) - Roose, Kathryn M.; Williams, W. Larry
ABSTRACT: In 1968 the first cohesive theory on goal setting proposed that difficult goals produce higher levels of performance than easy goals and that specific goals produce a higher level of performance than "do your best" goals. While over 40 years of research supports this theory, there has been some discrepancy regarding the use of very difficult goals. This study was designed to examine the effects on performance of different levels of performance improvement goals and two different types of feedback, as feedback is often used in conjunction with goal setting. A group design was used with participants receiving one of two goal levels, and two different types of feedback. While no significant effects were found between the two types of feedback, goal level produced significant results in terms of performance and accuracy.